The use of TiAlN coated carbide tool when finish machining hardened stainless steel. (17th October 2007) - Noordin, M.Y.; Tang, Y.C.; Kurniawan, D.
The introduction of hard turning has provided an alternative to the conventional processing technology used to manufacture parts made from hardened steels. Shorter product development time along with being more environmentally friendly are among the benefits offered by hard turning, which potentially results in lower manufacturing cost per part. However, common tool materials for hard turning applications are expensive. Due to the continuous developments in cutting tool materials and coating technology, inexpensive coated carbide cutting tools are being investigated to determine the potential of using them for use in extreme conditions as in hard turning. TiAlN coated carbide tool was selected to finish machine hardened steel. Performing hard turning dry at various cutting conditions, that is, cutting speed and feed rate, revealed that satisfactory tool life values and surface finish values that meet the strict range of finish machining were obtained when finish machining hardened steel of 47?48 HRC hardness.